2018
DOI: 10.3126/jgmcn.v10i2.20809
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude on Legalization of Abortion among Undergraduate Students

Abstract: Background: Abortion is public health concern in many parts of the world and is also contentious issue with religious, moral, cultural and political dimensions. Awareness program has most essential role to prevent the unusual death of mothers in the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
7
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 5 publications
6
7
2
Order By: Relevance
“…The result is comparable with a study done in Nepal which shows that most 88 (97.80%) of the respondents mentioned that Government approved Hospitals/clinics are the best place for providing abortion services. [10] This finding is also supported by a study done in Nepal where 84(68.9%) respondents stated that hospitals are the appropriate place for safe abortion. [15] A study done in Rajasthan, India among women who came for medical termination of pregnancy in a medical college revealed contradictory finding where 100(58%) of the respondents knew that safe abortions were performed at government approved institutions.…”
Section: Level Of Attitudesupporting
confidence: 58%
See 3 more Smart Citations
“…The result is comparable with a study done in Nepal which shows that most 88 (97.80%) of the respondents mentioned that Government approved Hospitals/clinics are the best place for providing abortion services. [10] This finding is also supported by a study done in Nepal where 84(68.9%) respondents stated that hospitals are the appropriate place for safe abortion. [15] A study done in Rajasthan, India among women who came for medical termination of pregnancy in a medical college revealed contradictory finding where 100(58%) of the respondents knew that safe abortions were performed at government approved institutions.…”
Section: Level Of Attitudesupporting
confidence: 58%
“…This finding is supported with the study conducted in Nepal among undergraduate students where, majority 75 (83.30%) respondents had correct knowledge on legally allowed time for safe abortion. [10] Another study also revealed the consistent finding where majority respondents 89 (73.0%) had correct knowledge that a pregnant woman can terminate pregnancy on her own will up to 12 weeks of gestation. [15] Regarding the especial condition that allowed for safe abortion, this study noted that among the respondents 195(62.9%) responded as when the life of woman or fetus are threatened followed by 163(52.6%) pregnancy resulted from incest or rape, 136(43.9%) if woman has physical or mental disabilities and 111(35.8%) if fetus has severe abnormalities.…”
Section: Level Of Attitudementioning
confidence: 71%
See 2 more Smart Citations
“…The study reveals that 94.4% of the students had the good knowledge regarding the abortion. 8 The knowledge about the abortion of present study was higher than the finding of Gyawali et al 9 where it was 78.4%.…”
Section: Discussioncontrasting
confidence: 72%